2022
DOI: 10.1038/s41598-022-06079-w
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and current rectification in a charged conical nanopore filled with viscoelastic fluids

Abstract: The ionic current rectification (ICR) is a non-linear current-voltage response upon switching the polarity of the potential across nanopore which is similar to the I–V response in the semiconductor diode. The ICR phenomenon finds several potential applications in micro/nano-fluidics (e.g., Bio-sensors and Lab-on-Chip applications). From a biological application viewpoint, most biological fluids (e.g., blood, saliva, mucus, etc.) exhibit non-Newtonian visco-elastic behavior; their rheological properties differ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Conversely, by increasing the λ D , resistive forces arise at the nanopore‘s tip, dampening the ionic current [65,66] . Compared to long nanopores, short nanopores have considerable advantages, including a higher ionic permeation coefficients and increased biosensor sensitivity [67] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, by increasing the λ D , resistive forces arise at the nanopore‘s tip, dampening the ionic current [65,66] . Compared to long nanopores, short nanopores have considerable advantages, including a higher ionic permeation coefficients and increased biosensor sensitivity [67] .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, by increasing the λ D , resistive forces arise at the nanopore's tip, dampening the ionic current. [65,66] Compared to long nanopores, short nanopores have considerable advantages, including a higher ionic permeation coefficients and increased biosensor sensitivity. [67] In order to improve energy conversion, desalination, and biosensor sensitivity, it is essential to achieve significant ICR in nanopores.…”
Section: Resultsmentioning
confidence: 99%
“…Non-Newtonian fluids also have a significant impact on the ICR phenomenon in nanochannels. Trivedi et al 50 used the simplified PTT (sPTT) model to study the effect of non-Newtonian fluids on flow and ion transport in individual conical nanopores. The results showed that the ICR phenomenon was promoted by both the ductility parameter and the Deborah number at high bias voltages and was more pronounced at low kR t values.…”
Section: Introductionmentioning
confidence: 99%
“…Berzina and Anand [34] described an electrokinetic means of producing dialysate from the excess fluid extant in the peripheral blood of patients undergoing therapy by using ICP. Trivedi and Nirmalkar [35] investigated ICP in charged cylindrical nanopore using viscoelastic fluids. Liu et al [36] investigated the interplay between ICP and process performance in the pervaporation operation for volatile organic component removal in a membrane channel with rectangular cross section.…”
Section: Introductionmentioning
confidence: 99%